Pengetahuan dan Pola Asuh Orang Tua Terbukti Meningkatkan Perkembangan Sosial Anak Dengan Retardasi Mental Di Maluku Tengah - Lameky, Vernando Yanry; Halalohun, Clemen; Lilipory, Mevy (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2024)
Background: Mental retardation is a general decline in intellectual function that occurs during child development and is associated with impaired social adaptation. Objective: The purpose of this study was to determine the relationship between knowledge and parenting styles of parents on the social development of children with mental retardation. Method: descriptive with cross sectional approach. The data collection technique used a total sampling of 44 respondents. Data were collected using a questionnaire and the Vineland Social Maturity Scale (VSMS). Results: The results of the Chi-Square test analysis showed p value = 0.039 (p≤0.05) for parental knowledge of children's social development and p-value = 0.012 (p≤0.05) for parenting patterns on child social development. Conclusion: The results of this study are used as a new program for nurses, the community and all stakeholders to improve the social development of children with mental retardation.Keywords: knowledge of social development; parenting; mental retardation